Demystifying the workers’ ratio of export oriented RMG Factories in Bangladesh: Perspective from Mapped in Bangladesh (MiB) - Shajahan, Sadril; Islam, MD. Faizul; Chowdhury, Fahim S; Ahmad, Faria (Centre for Entrepreneurship Development (CED), Brac University, 2021)
While it has been widely acknowledged that female workers account for 80% of the garments industry’s workforce in Bangladesh, there are also a number of studies and surveys that marked that have estimated different male to female workers’ ratios ranging from 35: 65 to 55:45. This paper aims to contribute to such debate by analyzing data of workers’ gender composition collected by the project ‘Mapped in Bangladesh’ (MiB).